29.6k views
3 votes
Graph the system of equations below and find the solution. y = 2x y = -x + 6

User MOrloff
by
4.4k points

2 Answers

0 votes

Answer:

(2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4) (2,4). The answer is (2,4).

User Djeetee
by
4.8k points
3 votes

Answer:

(2,4)

Explanation:

To graph, draw a straight line connecting:

(0,0) & (1,2) for y = 2x

(0,6) & (6,0) for y = -x + 2

y = 2x

y = -x + 6

2x = -x + 6

3x = 6

x = 2

y = 2x = 4

User Deepkimo
by
5.3k points